Pola Asuh Orang Tua dalam Membentuk Karakter Kedisiplinan Siswa Sekolah Dasar - wibowo, Ari Wibowo (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
This research is intended to determine the parenting patterns used by parents in shaping the disciplinary character of class V students at Tegalmulyo State Elementary School. This research was conducted using a qualitative method with a phenomenological approach. Data collection techniques use interviews, observation and documentation. The data analysis technique uses Miles and Huberman's steps which include data reduction, data presentation, drawing conclusions/data verification. The results of the research show that fifth grade students at State Elementary School Tegalmulyo are disciplined in carrying out activities at home and at school, although there are still some violations, but the percentage is relatively small. Then the parenting pattern used by parents of class V students at State Elementary School Tegalmulyo to shape the students' disciplinary character is a democratic parenting pattern based on existing characteristics. Apart from factors from parents and oneself, schools also have an important role in shaping student discipline. If parents will provide advice, direction and role models to form student discipline, then the school will provide it through action directions and also rules of conduct which contain obligations, prohibitions, sanctions and also rewards.